Les chrétiens d'Allah, une recherche vivante : une base de données de 1600 renégats à partir des archives de Lucile et Bartolomé Bennassar - Marianne Delacourt (Les Cahiers de Framespa)
How can a research from the end of the 1980s, composed of typed or handwritten forms, be a part of a Digital Humanities project and open up new perspectives ? The historian Bartolomé Bennassar had donated to the CollEx Iberian studies 1600 renegades’ index cards of the courts of the Inquisition, which served as a basis for the publication : " Les chrétiens d’Allah : l’histoire extraordinaire des renégats XVIe et XVIIe siècles/Bartolomé et Lucile Bennassar " These cards evoke the conditions of their denials, the circumstances of their appearance before the courts ... they were digitized and all of the data added to the base "Renégats”. Nowadays, available in free access, this database allows the questioning of the origin, the sex, and the way of life of these renegades, as well as their religious practice and their faith.